Examining the bidirectional nexus between financial development and green growth: International evidence through the roles of human capital and education expenditure. (December 2022) - Ngo, Thanh; Trinh, Hai Hong; Haouas, Ilham; Ullah, Subhan
Abstract: In the context of the 2030 Agenda for Sustainable Development by the United Nations, the functionality of financial development is undeniable in the wider economy toward Sustainable Development Goals (SDGs). Using novel panel data of 36 countries over the last decades, the study sheds light on the bi-directional nexus between financial development and green growth where human capital and education expenditure present their central roles in sustainable development. The study provides critical findings to the existing literature on climate change, environment, and sustainability. Following the empirical findings, we provide important insights to regulators, policy makers, and organizations in investigating the substantial contributions of financial development including financial markets and financial institutions where their accessibility, depth, and efficiency need a thorough consideration toward SDGs and mitigating climate change impacts worldwide. Apart from using the multidimensional proxies, the empirical findings are validated by a set of econometric approaches. Highlights: The study presents a bi-directional nexus between financial development (FD) and green growth (GG). Using international evidence from 36 countries, the bi-directional nexus between GG and FD is affirmed through a set of several econometric models. Human capital (HC) and education expenditure (EE) present their central roles in the GG-FD nexus across countries and regions. Financing sustainable infrastructure is an undeniable critical factor in the trajectories between GG and FD in the United Nations' 2030 Agenda for Sustainable Development. Sustainable infrastructure investments in the era of climate change are crucial to economies with high climate risk exposure due to employing heavily non-renewable sources of energy.